Artificial bone scaffolds of coral imitation prepared by selective laser sintering. (April 2020) - Shi, Yunsong; Pan, Teng; Zhu, Wei; Yan, Chunze; Xia, Zhidao
Abstract: Coralline hydroxyapatite (CHA) has been used in clinical for over 20 years. However, coral is an endanger species and has been banned from mining. In addition, coral artificial bone has slow biodegradation of the defects, hindering the growth of new bone. In order to explore the natural coral artificial bone substitute materials, this work proposed using Selective Laser Sintering (SLS) to fabricate natural calcium carbonate/biopolymer composite imitation coral porous structures, and then the surface of the 3D printing product was transformed into a hydroxyapatite thin layer by hydrothermal conversion reaction. The mechanical properties and porosity were optimized by adjusting the SLS processing parameters including laser power, scanning speed and layer thickness. In the composites with the PLLA of 15 wt%, the SLS processing parameters with the laser power of 15 W, laser scanning speed of 1500 mm/s and single layer thickness of 0.08 mm result in the better mechanical properties. After hydrothermal conversion, the products were confirmed to be a mixture of hydroxyapatite (HA) and calcium carbonate by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and energy dispersive X-ray spectroscopy (EDX). The TGA results revealed that increasing the reaction temperature or prolonging the reaction time can increase the degree of hydrothermal reaction and thus promote the transformation of calcium carbonate into hydroxyapatite. The results of cytotoxicity assay and Life/Dead staining showed that the scaffold is not toxic to L929 cells. This work has the materials system innovation and focuses on the study of the effects of the SLS and hydrothermal processes on the mechanical performance and the degree of hydroxylation. Then, the preparation process of imitation coral artificial bone preparation was optimized. it is concluded that the imitation coral artificial bone is a nontoxic biomaterial; however, further study on its osteogenic capacity should be warranted in the future.